Cultural Implementation of Punggahan in the Pujakesuma Organization: a Sociocultural Study in Medan City - Prinsi Rigitta (Sean Institute, 2025)
This study aims to determine how the Pujakesuma organization maintains the punggahan tradition as one of the Javanese cultural heritages in Medan City. Punggahan is a Javanese tradition performed before the month of Ramadan as a form of respect for ancestors and self-purification. This study uses a qualitative approach with data collection techniques in the form of participatory observation, in-depth interviews, and documentation. The theories used are Koentjaraningrat's Culturalism and Emile Durkheim's theory of religion as a social institution. The results show that Pujakesuma actively preserves the punggahan tradition by involving all elements of the Javanese community, especially the younger generation, and adapting the form of implementation to remain relevant in the modern era.